AB0890 Relationship between chronic low back pain and MRI of sacroiliac joints. (23rd January 2014) - Calvo, J.; Collantes, E.; Font, P.; Castro, M.C.; Escudero, A.
Abstract : Background: RELATIONSHIP BETWEEN CHRONIC LOW BACK PAIN AND MRI OF SACROILIAC JOINTS Objectives: To determine the relationship between chronic low back pain and presence of edema on MRI of sacroiliac joints and to establish the value of MRI as a method of early diagnosis of SpA without considering others characteristics Methods: An Observational cross-sectional study, which included 95 patients with chronic low back pain suggestive of spondyloarthritis from primary care, was carried out. The criteria for inflammatory back pain were aplicated to these patients and the relationship between chronic inflammatory back pain according to (PCM) prymary care physicians (gold standar) and the presence or absence of signs of inflammatory activity in MRI, was assessed. Results: Results: 51.6% of the patients were male, with a mean age of 32.6 (8.86) years, 84'2% of patients fulfilled the criteria for inflammatory back pain according to PCM. Their mean evolution time was 8.43 (16.5) months. 42.1% showed HLA-B27 and only 22.1% had a family history of spondyloarthritis. Of the group of patients who fulfilled PCM criteria for inflammatory back pain, 42 (44.2%) showed RM SI joint (+). No differences in age, gender or form onset of symptoms in another group (with edema or without edema), wasn't fond. However, a prevalence of HLA B27 (57'8% vs. 24'5%) p=0.001, night waking in 2nd half of the night (64'4% vs 18.4% p=0.0001), morning stiffness>1 hour (73.3% vs. 40'8%, P=0.001) and pain in alternating buttocks (42'2% vs. 14'3%, P=0.002), were recorded. The number was higher if the criteria was classified according to the experts. The MRI showed edema in 52'5% patients classificated of inflammatory by PCM criteria, increasing it to 67% if applied to experts' criteria. This means that nearly half of the patients classified by the PMC had negative MRI Conclusions: Although MRI appears to be a safe and useful tool to detect inflammatory lesions in patients with early axial SpA and thus is widely used in clinical practice (having been included it in the new classification criteria) data was from our study indicates that in cases of chronic low back pain, if not properly classified as inflammatory, MRI is not sensitive. Therefore, in clinical practice (outside of clinical trials) the RM has no value, and it implies the need to incluid other more sensitive markers and/or other clinical or laboratory caracteristics to establish the diagnosis in the early stages of the disease. References: Rudwaleit, M. et al. Ann. Rheum. Dis. 68, 770–776(2009) Rudwaleit M, van der Heijde D, Landewé R, et al. Ann Rheum Dis2009; 68: 777–83. M. Rudwaleit, A. G. Jurik, K-G A Hermann. Ann Rheum Dis. January, 2009; 68; 1520–1527. M. Rudwaleit, A. G. Jurik, K-G A Hermann. Ann Rheum Dis. January, 2009; 68; 1520–1527. N Bennett, A Rehman, E M A Hensor, H Marzo-Ortega, P Emery, D McGonagle. Ann Rheum Dis 2010;69:891–8942 Disclosure of Interest: None Declared